Mapeamento de egressos a partir do Currículo Lattes: estudo de caso do curso de Biblioteconomia e Ciência da Informação da Universidade Federal de São Carlos - Lozano, Marisa Cubas (Universidade Federal de São Carlos, 2023)
Public Higher Education Institutions (HEI) have a social commitment to training people, and this commitment must also extend after graduation. Graduates, defined in this study as those who have already completed their courses, represent one of the main assets of these institutions, making the implementation of policies and methodologies essential for the continuous monitoring of the progress of their post-training activities. Monitoring graduates is a tool that benefits graduates and the HEI, as it is possible, for example, to offer advantages to these individuals; measure the success of an institution; understand the market and employability; evaluate the course and the institution; continue with the commitment to training people and obtaining information to meet higher education accreditation and evaluation systems. Furthermore, monitoring graduates can provide indicators on the performance of an HEI, as well as the return on public investment made in the institution. Recognizing the relevance of this monitoring, this thesis proposed to map the graduates of the undergraduate course in Librarianship and Information Science at the Universidade Federal de São Carlos (UFSCar) based on data made publicly available in the Currículo Lattes, in addition to data obtained directly from the institution. To this end, a case study was carried out with UFSCar graduates, detailing the information obtained about graduates of the undergraduate course in Librarianship and Information Science entering between the years 1994 and 2016. Using the LattesMachine tool, it was possible automatically extract the Currículo Lattes files of graduates who registered on the Lattes Platform. The resulting information was processed with the aid of VantagePoint software and the Python Programming Language. As a result, information was obtained about the employability and continuing education of all graduates and analyzed in detail the information about graduates of the Librarianship and Information Science course. The combination of data from the Currículo Lattes and information obtained from UFSCar systems proved to be effective both in responding to performance assessments of HEI and in monitoring graduates and understanding the social impact of these institutions. Therefore, it is recommended to enrich this data with the incorporation of data from other government sources and other internal systems of the HEI itself, in order to improve the monitoring of graduates and, thus, add more elements for institutional excellence for the benefit of society.
Mapping of graduates based on the Lattes Curriculum: case study of the Librarianship and Information Science course at the Universidade Federal de São Carlos
Keywords: Egressos; Acompanhamento de egressos; Currículo Lattes; Graduates; Monitoring graduates; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA